(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article analyzes the issue of the reliability of ḥadīth, the second primary source of Islam, focusing specifically on the problem of “mawdu” or “fabricated” ḥadīths in ḥadīth studies. The article elucidates the essence of the term “mawdu ḥadīth”, its definition and description within hadith scholarship. It also examines the various reasons behind hadith fabrication, such as political conflicts, sectarianism, personal interests, ignorance, or the actions of enemies of Islam. The article discusses individuals known for fabricating ḥadīths and the views and methods of scholars of Jarh wa Taʼdil (criticism and validation of narrators), such as Ibn Ḥajar al-ʿAsqalānī, which are crucial for identifying them.